Kajian Kebijakan PMW (Program Mahasiswa Wirausaha) - Hendarman -- (Jurnal Pendidikan dan Kebudayaan, 2011)
The government through the Ministry of National Education in 2009 has launched a special program for students at higher education institutions the so-called â€œProgram Mahasiswa Wirausaha (PMW)â€. This program aims for facilitating studentsâ€™ interest and talent in entrepreneurship to be an entrepreneur based on their disciplines in science, technology and arts. This program is also to respond to the fact that big percentages of higher education graduates become job-seeker instead of job-creator. This program provides students with grant either in person or in a group. This article analyses the implementation of PMW in the view of those students who took part in the program with two focuses, namely the importance of PMW and the achievement of studentsâ€™ grant-receiver. The respondents were from both public and private higher education institutions. The analysis revealed that the program have significant impact in broadening studentsâ€™ perspective, competences and attitude to be an enptreneur, as well as opening new job-market for people. It is suggested to conduct another evaluation to analyse the appropriateness of grant given to students and financial allocation for each higher education institution by taking into consideration the total number of students and number of success students in PMW.Â ABSTRAKSuatu program khusus bagi para mahasiswa yaitu Program Mahasiswa Wirausaha (PMW) telah diluncurkan oleh Pemerintah melalui Kementerian Pendidikan Nasional pada tahun 2009. Kebijakan ini dimaksudkan untuk memfasilitasi para mahasiswa yang mempunyai minat dan bakat kewirausahaan untuk memulai berwirausaha dengan basis ilmu pengetahuan, teknologi dan seni yang sedang dipelajarinya.Â Keberadaan program ini didukung oleh kenyataan bahwa sebagian besar lulusan Perguruan Tinggi adalah lebih sebagai pencari kerja daripada pencipta lapangan pekerjaan. Program ini memberikan bantuan bagi mahasiswa yang layak dalam bentuk dana yang dapat digunakan secara perorangan dan kelompok. Tulisan ini merupakan kajian terhadap kebijakan PMW ditinjau dari persepsi mahasiswa terhadap pentingnya PMW dan keberhasilan usaha wirausaha mahasiswa. Responden kajian ini adalah para mahasiswa penerima bantuan PMW di beberapa perguruan tinggi negeri dan swasta. Temuan kajian adalah bahwa program ini memiliki dampak penting yaitu membuka wawasan, kemampuan dan sikap mahasiswa dalam bewirausaha, serta membuka lapangan kerja bagi masyarakat. Evaluasi lebih lanjut terhadap besarnya hibah bagi masing-masing mahasiswa dan alokasi dana bagi perguruan tinggi perlu dikaji dengan memperhitungkan jumlah total mahasiswa dan keberhasilan mahasiswa PMW pada tahun sebelumnya di masing-masing perguruan tinggi.